Current patterns and distribution of suspended solids on the sea coast - Nugroho, Iwan; Sulaiman, Fatah; Sjaifuddin, Sjaifuddin (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
The ocean faces a variety of environmental challenges, including pollution, overfishing, habitat destruction, and climate change. These threats can have significant impacts on marine ecosystems and the livelihoods of coastal communities. The sea is also affected by currents, which are the continuous and directional movement of seawater. A number of variables, including wind, temperature, salinity, and the earth's rotation, influence ocean currents. Ocean current patterns are complex and can vary greatly depending on the region and time of year. Ocean current patterns can significantly impact the distribution and movement of suspended solids in the ocean. High levels of suspended solids can reduce water clarity, making water appear cloudy. The value of the concentration of suspended solids in a body of water greatly affects how high its turbidity is. Hydrodynamic models are used to study the movement of water and sediment in estuaries and coastal areas, including tidal, wave, and current effects. Understanding the movement of suspended solids in the ocean is important because it can help predict the spread of pollutants, determine sediment transport patterns, and understand the impact of suspended solids on marine ecosystems.Keywords:Current patternsSuspended solidsHydrodynamicsSea coast